Influence of Fertilizer Types on Seed Quality Aspects of Indigenous Vegetables - Letting , F.K; J.O , Ochuodho; E , Omami (African Journal of Education,Science and Technology (AJEST), 2018)
Indigenous vegetables play an important role in most families in Western Kenya. The management practices that the farmer uses during its seed production has a greater effect on the final seed obtained. Fertilizer application has been determined to be the basic input that contributes to the final seed quality. This experiment was set out to determine the effects of different fertilizer types on the seed aspects of three AIVs. The experiment was laid out in a split plot in a Randomized Complete Block Design with three replications at the University of Eldoret farm. Three species were subjected to two fertilizer types: chicken manure (organic) and mavuno fertilizers (inorganic). Three plants in each of the varieties of spider plant and Amaranthus planted were tagged randomly. The silique lengths of the spider plant varieties, the inflorescence length of the Amaranthus were measured. Thousand seed weight of seeds of the three species was also done. Seeds of these species were kept at 4°C temperature for seven months then tested for the germination potential. The data obtained was then analyzed by Genstat software and the separation of means done by Tukey’s. The silique lengths did not vary significantly among the three different types of fertilizers used (P>0.05). However, the inflorescence lengths of the Amaranthus species differed significantly (P<0.05). There was a significant difference in the germination potential of seeds in which fertilizer had been used during planting (P<0.05). In all the three varieties, the use of fertilizers resulted in increased germination potential. The thousand seed weight of the three species differed significantly in spider plant and black night shade but not in Amaranthus. The use of chicken manure leads to increase in the length of inflorescence of Amaranthus species; thousand seed weight of spider plant and black night shade but it has no effects on silique lengths of spider plant and thousand seed weight of Amaranthus